An epidemiological study of the respiratory health of workers in the European refractory ceramic fibre industry. Issue 12 (1st December 2001) - Cowie, H A; Wild, P; Beck, J; Auburtin, G; Piekarski, C; Massin, N; Cherrie, J W; Hurley, J F; Miller, B G; Groat, S; Soutar, C A
Abstract : OBJECTIVES: To investigate possible relations between respiratory health and past airborne exposure to refractory ceramic fibres (RCFs) and respirable dust in workers at six European factories, studied previously in 1987. METHODS: The target population comprised all current workers associated with RCF production, plus others who had participated in 1987 "leavers". Information was collected on personal characteristics, chest radiographs, lung function, respiratory symptoms, smoking, and full occupational history. Regression analysis was used to study relations between indices of health of individual workers and of cumulative exposure to airborne dust and fibres, and likely past exposure to asbestos. RESULTS AND DISCUSSION: 774 workers participated (90% of current workers, 37% of leavers). Profusion of small opacities in exposed workers (51% 0/1+; 8% 1/0+) was similar to that among an unexposed control group but higher than in new readings of the 1987 study films (11% 0/1+, 2% 1/0+). The large difference between 1987 and recent films may be, at least in part, a reading artefact associated with film appearance. Small opacities of International Labour Organisation (ILO) category 1/0+ were not associated with exposure. An association of borderline significance overall between 0/1+ opacities and exposure to respirable fibres was found for some exposure periods only, the time related pattern being biologically implausible. Pleural changes were related to age and exposure to asbestos, and findings were consistent with an effect of time since first exposure to RCFs. Among men, forced expired volume in 1 second (FEV1 ) and forced vital capacity (FVC) were inversely related to exposure to fibres, in current smokers only. FEV1 / FVC ratio and transfer factor (TLCO ) were not related to exposures. The estimated restrictive effect was on average mild. Prevalence of respiratory symptoms was low. Chronic bronchitis and its associated symptoms (cough, phlegm) showed some association with recent exposure to respirable fibres. This could be due to an irritant effect of RCFs.